PERFORMANCE EVALUATION OF THE IRD RSUP DR. SARDJITO BUILDING TO THE INFLUENCE OF EARTHQUAKE - T. S.M. Aritonang; I. Satyarno; B. Supriyadi (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2011)
In performance-based design, the level of performance of hospital buildings is generally operational, where the buildings are expected to continue to function after the occurrence of the earthquake and do not undergo significant damage. This research evaluates the level of performance suitability of the Emergency Care Installation Buildings of Dr. Sardjito Hospital (hereinafter referred to as IRD RSUP Dr. Sardjito building) for the effects of earthquakes. First evaluation is done by Rapid Visual Screening by FEMA 154 (2002), then continued with more detailed evaluation based on FEMA 310 (1998). The building structure is modeled by SAP2000 and created in 2 models, i.e. the Models with wall and the Models without wall. The earthquake loads refers to SNI 1726-2002. The strength of structural elements is calculated with SNI 2847-2002 and Response-2000. For evaluation of structure performance levels, a pushover analysis used for nonlinear procedures, where the analysis used to the Seismicity region 3 and 4. Performance point is determined by Capacity Spectrum Method based on ATC-40 (1996), which has built-in in the SAP2000 Program. The performance level of the building is determined by drift ratio criteria required by FEMA 356 (2000) as well as ATC-40 (1996). From the research results, it is obtained that the natural period for the Model with wall is 0.592 seconds and 1.687 Hz frequency, and natural period for Model without wall is 1.291 seconds and 0.774 Hz frequency. Therefore, the level of structure performances for earthquake return period of 500 years is immediate occupancy.